2015
DOI: 10.1097/ta.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital interventions in severely injured pediatric patients

Abstract: Care management/therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
0
20
0
1
Order By: Relevance
“…The evidence supporting the systematic Airway, Breathing, and Circulation (ABC) approach to injured patients is based on expert consensus with little literature to support the clinical application of the order in which this sequence should be applied [ 1 ]. Early intubation can result in deleterious effects in adult and pediatric patients with traumatic brain injury [ 2 6 ]. There are many physiological explanations why intubation in hypovolemic shock might result in worse perfusion [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence supporting the systematic Airway, Breathing, and Circulation (ABC) approach to injured patients is based on expert consensus with little literature to support the clinical application of the order in which this sequence should be applied [ 1 ]. Early intubation can result in deleterious effects in adult and pediatric patients with traumatic brain injury [ 2 6 ]. There are many physiological explanations why intubation in hypovolemic shock might result in worse perfusion [ 2 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early intubation can result in deleterious effects in adult and pediatric patients with traumatic brain injury [ 2 6 ]. There are many physiological explanations why intubation in hypovolemic shock might result in worse perfusion [ 2 6 ]. After rapid sequence intubation (RSI), there is a vasodilatory response placing the hypovolemic patient at very high risk for more pronounced hypotension and decreased perfusion [ 7 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood was shown to provide balanced resuscitation much more quickly at a civilian pediatric hospital compared to using components . However, data on the appropriate indications and outcomes of pre‐hospital use of blood products for pediatric patients, specifically for infants, are lacking . While there is no physiologic reason not to use whole blood in children with life‐threatening hemorrhage, the decision to transfuse whole blood to an infant is challenging due to the relative paucity of evidence supporting the use of whole blood for pediatric patients and the lack of specific guidelines for pediatric damage control resuscitation, as well as the decision regarding the volume of LTOWB to transfuse .…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of adult traumatic cardiac arrest patients, Kleber et al report missing or insufficient chest decompression in 37% of the patients with tension pneumothorax [14]. In a retrospective analysis of children injured during the Afghanistan war, Sokol et al found that only 14/95 patients with an indication for pleural decompression received a prehospital intervention [15]. Especially in children, experience of Emergency Medicine Service (EMS) personnel performing needle decompression is scarce, let alone open finger thoracostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to publication bias the true rate is most likely clearly higher. In their aforementioned work, Sokol et al report of 16 prehospital pleural decompressions in children, of which 2 (12.5%) were performed without a clear indication [15]. These data show that a false positive diagnosis of tension pneumothorax has to be considered and the risk of injury to intrathoracic vital structures has to be taken into account when choosing the site for needle decompression.…”
Section: Discussionmentioning
confidence: 99%